Synthesis of N-thioacylated amino sugars - Isecke, Rainer; Brossmer, Reinhard (Tetrahedron, 1993)
Unsubstituted amino sugars readily react with dithiocarboxylic ester or O-ethyl thioformate to yield the hitherto unknown free N-thioacylated sugars which are of biological interest.
Elektronische Reproduktion der Druck-Ausgabe 15. Mai 2001
Gesehen am 24.06.2024